2020
DOI: 10.1002/pits.22469
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of real‐time and delayed visual performance feedback on teacher praise

Abstract: A number of researchers have found behavior‐specific praise (BSP) to be an effective strategy for increasing student academic engagement. Performance feedback is often used to promote teacher BSP; however, variations in how performance feedback is provided have been proposed and it is unknown whether one strategy may be more effective than others. The current study compared two types of performance feedback, delayed performance feedback and real‐time visual performance feedback, on the use of BSP by Head Start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This application, referred to as Periodic Service Review (PSR), includes the clear step-by-step description of how each procedure is to be implemented, the competency-based criterion referenced training of the relevant service providers responsible for the procedure’s implementation, monitoring of the service providers' implementation through formal fidelity checks, and visual feedback graphs over time that show what percentage of the plan is being implemented consistently. Research has shown that such visual feedback graphs motivate staff to improve their performance (Lown et al, 2021 ; Quilitch, 1975 ). An unmet criterion is characterized as an opportunity to improve service quality (a good thing) rather than as an indicator of poor performance (a bad thing).…”
Section: Mebs Implementationmentioning
confidence: 99%
“…This application, referred to as Periodic Service Review (PSR), includes the clear step-by-step description of how each procedure is to be implemented, the competency-based criterion referenced training of the relevant service providers responsible for the procedure’s implementation, monitoring of the service providers' implementation through formal fidelity checks, and visual feedback graphs over time that show what percentage of the plan is being implemented consistently. Research has shown that such visual feedback graphs motivate staff to improve their performance (Lown et al, 2021 ; Quilitch, 1975 ). An unmet criterion is characterized as an opportunity to improve service quality (a good thing) rather than as an indicator of poor performance (a bad thing).…”
Section: Mebs Implementationmentioning
confidence: 99%